Menghidupkan yang Mati Suri: - Qadafy, Mu'ammar Zayn (Lajnah Pentashihan Mushaf Al-Qur'an, 2022)
This article outlines several main ideas underlying Walid Saleh's works from 2004 to the present, including the genealogical nature of tafsir materials and the dichotomy of medieval tafsir books into encyclopaedic and Madrasa categories. The article reveals the grand goal of Saleh's scholarship, which is redirecting the intellectual history of tafsir that has been - according to him - covered by an intellectual movement that adores Ibn Taymiyyah and his radical hermeneutic. By evaluating Saleh's articles and books, this article concludes that his ideas are very relevant to be studied in the PTAI curricula, especially developing the major of Qur'an and Tafsir sciences, so that the study of medieval tafsir finds its way back to the Indonesian academic context after being neglected for a period of time.